Problem based learning in the online classroom - Palner, Mikael (Improving University Science Teaching and Learning, 2023)
Problem based learning (PBL) is the teaching about a subject evolving around a central problem or case study. It was originally designed to increase learning for medical students in the mid- 1960s, where medical problems were presented to the students, who had to figure out what diagnosis to give (Norman & Schmidt, 1992). In this essay I will examine how PBL can be adapted to teaching in basic science as well as the online classroom.